Exploring consumer behaviour and perceptions - Loku, Nadire (Central European Public Administration Review, 2025)
Purpose: This study examines consumer perceptions, attitudes, and behavioural responses to Enterprise Social Responsibility (ESR) within Kosovo’s developing market. Design/methodology/approach: Drawing on structured quantitative survey data (n = 182), the research analyses how demographic characteristics—in particular gender, age, education, and economic status— influence consumers’ understanding and evaluation of ESR practices. Although there is broad conceptual support for socially responsible business conduct, actual consumer behaviour remains contingent on product related factors such as quality, price, and availability. Findings: The study identifies a significant attitude-behaviour gap, revealing a disconnect between ethical preferences and market actions. Furthermore, consumers display limited trust in self promotional ESR campaigns, favouring externally validated or regulatory driven approaches. These findings underscore the critical role of transparency and authenticity in enhancing consumer trust and highlight the need for ESR strategies that are both context sensitive and institutionally anchored. Originality/significance/value: The study offers actionable insights for policymakers and practitioners seeking to strengthen corporate social responsibility frameworks and foster more sustainable consumer–enterprise relationships in transition economies.
Keywords: attitude-behaviour gap; consumer behaviour; corporate ethics; corporate social responsibility; družbena odgovornost podjetij; enterprise social responsibility; podjetniška družbena odgovornost; poslovna etika; preglednost; sustainability; trajnost; transparency; vedenje potrošnikov; vrzel med stališči in ravnanjem